Predictors of blastocyst formation rate in elective day 5 transfer cycle. (17th August 2020) - Hong, Yeon Hee; Kim, Hye Kyeong; Nho, Eun Jee; Youm, Hye Won; Kim, Seul Ki; Lee, Jung Ryeol; Jee, Byung Chul; Kim, Seok Hyun
Abstract: This study aimed to investigate the factors affecting blastocyst formation rate. One hundred and seven fresh in vitro fertilisation (IVF) and elective day 5 blastocyst transfer cycles were selected. Univariate and multivariate analyses revealed that intracytoplasmic sperm injection (ICSI) ( r = −.236, p = .014 vs. p = .005) was advantageous for blastocyst formation. In addition, the number of mature oocytes ( r = −.274, p = .004 vs. p = .002) was a significant factor associated with blastocyst and good-quality blastocyst formation rates ( p = .021, r = −.389). Both blastocyst and good-quality blastocyst formation rates were significantly higher with ICSI than with conventional insemination (65.0 ± 24.5% vs. 50.0 ± 21.2%, p = .012; 43.1 ± 22.8% vs. 30.9 ± 19.8%, p = .038, respectively). The number of mature oocytes appears to be the most important predictor of blastocyst formation rate. Additionally, ICSI fertilisation is superior to conventional insemination in terms of blastocyst formation rate. IMPACT STATEMENT: What is already known on this subject? There are many advantages of blastocyst transfer cycle over cleavage transfer cycle, but there are no known routine selection criteria for the timing of embryo transfer. To date, the number of blastomeres, number of retrieved oocytes, quality of embryos and fertilisation method have been suggested as the important factors involved in blastocyst formation. However, the number of studies on this issue is limited, and some studies have shown conflicting results. What do the results of this study add? This study showed that the number of mature oocytes and ICSI fertilisation are the significant factors associated with blastocyst formation rate in elective day 5 transfer cycle. What are the implications of these findings for clinical practice and/or further research? This paper demonstrated that the number of mature oocytes and the fertilisation method should be considered before embryo transfer. Consideration of these factors would be meaningful in selecting patients who will be suitable for extended culture up to day 5.